Bite force, masticatory efficiency and nutritional status of individuals with Treacher Collins Syndrome - Medeiros, Laís Hollara (2020)
Introduction: Treacher Collins syndrome (TCS) is a congenital condition which main manifestations are zygomatic and mandibular hypoplasia, associated or not with a cleft lip and palate, leading to impairment in functions such as respiration and mastication. Objective: To characterize the stomatognathic system of individuals with TCS by assessing bite force and masticatory efficiency, and, additionally, to evaluate the nutritional status of this population through anthropometric measurements. Material and Methods: Forty-one individuals were evaluated, divided into 2 groups: 1) Control Group (CON): 20 adult individuals without TCS and with class I skeletal pattern, 2) Treacher Collins Syndrome Group (TCS): 21 adult individuals with TCS, regularly enrolled at HRAC-USP. In order to evaluate the stomatognathic system, two methods were adopted: 1) bite force measurement using a gnathodynamometer (IDDK Kratos, Cotia-SP, Brasil), and, 2) masticatory efficiency, through the measurement of the particles size of food submitted to standard chewing cycles (Image J - National Institutes of Health NIH). Nutritional status was assessed based on the following anthropometric parameters: 1) Weight, 2) Height, 3) Body Mass Index (BMI). Results: Means values of BF for the CON and the TCS groups corresponded to 431,6±134,1N and 170,9±109,4N (right molar), respectively, and, 427,4±147,8N and 171,2±93,9N (left molars), respectively. These differences were statistically significant. The mean particle size of the CON and TCS corresponded to 0,66±0,52 mm² and 1,58±1,93 mm². Although more than 2 times greater for the TCS group, this difference was not considered statistically significant. On both groups, statistically similar BMI were observed and corresponded to 23,4±4,7 (CON) and 23,4±6,1 (TCS). Underweight individuals were only observed on TCS group (24%). Conclusion: Individuals with Treacher Collins Syndrome presented with a reduced bite force and a reduced masticatory efficiency when compared to the control population, suggesting that the syndrome and its mandibular underdevelopment negatively impact masticatory function